Perancangan User Interface dan User Experience Aplikasi Pemandu Wisata Kebun Binatang Menggunakan Metode User Centered Design - Muhamad Ifan Nuriyana; Eko Setia Budi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
The development of technology in recent years has transformed the way humans interact with computers and has extended to various aspects of life, including the tourism sector, contributing to the distribution of more interactive information about tourist attractions, particularly through mobile applications. One of the emerging applications is the zoo tour guide application. Based on questionnaire results and processed using the System Usability Scale (SUS) method with an average score of 99.5 and a rating of "Excellent," an application was created and evaluated, known as the Zoo Tour Guide Application, to enhance the User Centered Design (UCD) approach. The design process involved wireframing and resulted in a prototype. The evaluation indicated that users could successfully navigate the testing scenarios. The UI/UX design yielded three main requirements for the application: animal page, map page, and ticket page.